2017
DOI: 10.3201/eid2308.170600
|View full text |Cite
|
Sign up to set email alerts
|

Human Infection with Highly Pathogenic Avian Influenza A(H7N9) Virus, China

Abstract: The recent increase in zoonotic avian influenza A(H7N9) disease in China is a cause of public health concern. Most of the A(H7N9) viruses previously reported have been of low pathogenicity. We report the fatal case of a patient in China who was infected with an A(H7N9) virus having a polybasic amino acid sequence at its hemagglutinin cleavage site (PEVPKRKRTAR/GL), a sequence suggestive of high pathogenicity in birds. Its neuraminidase also had R292K, an amino acid change known to be associated with neuraminid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
125
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(130 citation statements)
references
References 20 publications
3
125
0
Order By: Relevance
“…Though the case fatality rate and severity in humans were similar between highly pathogenic and low pathogenic H7N9 strains [2, 23], highly pathogenic H7N9 exhibited a R292K mutation, where an amino acid change had occurred that was known to be associated with neuraminidase inhibitor resistance. This lead to severe and complicated clinical sequelae [5, 24, 25]. The rapid geographical expansion and genetic evolution of the HPAI H7N9 viruses pose a great challenge, not only for poultry production but also for public health [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the case fatality rate and severity in humans were similar between highly pathogenic and low pathogenic H7N9 strains [2, 23], highly pathogenic H7N9 exhibited a R292K mutation, where an amino acid change had occurred that was known to be associated with neuraminidase inhibitor resistance. This lead to severe and complicated clinical sequelae [5, 24, 25]. The rapid geographical expansion and genetic evolution of the HPAI H7N9 viruses pose a great challenge, not only for poultry production but also for public health [26].…”
Section: Discussionmentioning
confidence: 99%
“…The 2017 isolate also possessed an R292K substitution in the neuraminidase protein, which confers oseltamivir resistance [5]. Animal experiments showed that these novel HPAI H7N9 variants were both highly pathogenic in chickens and lethal to mice.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to urban residents, rural residents usually have higher likelihood of exposure to sick or dead poultry, which were attributed to the popular country lifestyle of raising backyard poultry in China 5, 20, 21, 22. The human cases of infection with highly pathogenic avian influenza (HPAI) A(H7N9) virus have been found in Guangxi, Guangdong, and Hunan Provinces during the fifth wave 23, 24, 25. So far, there were no human cases of infection with HPAI A(H7N9) virus confirmed in Zhejiang province.…”
Section: Discussionmentioning
confidence: 99%
“…Although maintaining dual receptor-binding preference, their HA antigenicity was distinct from LPAI A (H7N9). Furthermore, NA R292K conferred a multidrug resistance phenotype (13).…”
Section: Human Infections Due To a Novel Avian Influenza A (H7n9)mentioning
confidence: 99%